2021
DOI: 10.1177/00207640211037722
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, disability, and dementia risk: Results from the Hispanic Established Populations for the Epidemiologic Studies of the Elderly (H-EPESE)

Abstract: Background: Emerging research has elucidated pathophysiological relationships among diabetes, disability, cognitive impairment, and incident dementia. However, the relationships between diabetes, disability, and dementia have been largely underexamined in Latino populations, which have a disproportionate prevalence of diabetes and its complications. Aims: This study examines diabetes as a risk factor for subsequent disability and dementia risk in a Mexican-origin older adult sample. Methods: The data are drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…We found that physical function impairment existed in nearly one-third of subjects in the total population, with a prevalence of 37.28%. This result was similar to the data of Vásquez et al [28] performed in 3050 older individuals from the Hispanic Established Populations for Epidemiologic Study and Farías-Antúnez et al [29] performed in 1451 elderly individuals from Brazil. However, this disability rate was obviously lower than those from a nationwide population-based longitudinal survey of a healthy aging study, which was selected randomly in 22 provinces in China [30] .…”
Section: Discussionsupporting
confidence: 91%
“…We found that physical function impairment existed in nearly one-third of subjects in the total population, with a prevalence of 37.28%. This result was similar to the data of Vásquez et al [28] performed in 3050 older individuals from the Hispanic Established Populations for Epidemiologic Study and Farías-Antúnez et al [29] performed in 1451 elderly individuals from Brazil. However, this disability rate was obviously lower than those from a nationwide population-based longitudinal survey of a healthy aging study, which was selected randomly in 22 provinces in China [30] .…”
Section: Discussionsupporting
confidence: 91%